FAKTOR PENENTU KEPUASAN LAYANAN DAN LOYALITAS PELANGGAN JASA PENERBANGAN PT. LION AIR DI MAKASSAR - Noce Fredy Maspaitella (EKONOMI & SOSIAL, 2013)
Determinants of Satisfaction and Customer Loyalty PT Lion Air Flight Services This study aims to identify and analyze 1) Effect of service quality, reasonable price, psychology, and the image of the company directly have a positive and significant impact on customer service satisfaction and loyalty PT Lion Air in Makassar, 2) the direct effect of service satisfaction has positive and significant on customer loyalty PT Lion Air in Makassar, 3) effect of service quality, reasonable price, psychology, and the company's image indirectly have a positive and significant impact on customer loyalty through service satisfaction PT Lion Air in Makassar.This study aims to identify and analyze 1) Effect of service quality, reasonable price, psychology, and the image of the company directly have a positive and significant impact on customer service satisfaction and loyalty PT Lion Air in Makassar, 2) the direct effect of service satisfaction has positive and significant on customer loyalty PT Lion Air in Makassar, 3) effect of service quality, reasonable price, psychology, and the company's image indirectly have a positive and significant impact on customer loyalty through service satisfaction PT Lion Air in Makassar.The population in this study were all domestic airline Lion Air passengers with a destination and departure Makassar. The number of samples as many as 100 people. Sampling technique using accidental sampling. Methods of analysis using path analysis. Research results indicate that the quality of service, the reasonableness of the price, psychology, and the image of the company directly have a positive and significant impact on service satisfaction and customer loyalty. Satisfaction is positive and significant direct effect on customer loyalty. Quality service, reasonable prices, psychology, and the company's image indirectly have a positive and significant impact on customer loyalty through service satisfaction PT Lion Air in Makassar.